Optimalisasi Penerimaan Pajak Bumi dan Bangunan di Kota Pontianak - B01108099, Jonni Muliardi (Jurnal Pembangunan dan Pemerataan, 2014)
This research was done in order to analyze the optimization of land and building tax income in the city of Pontianak. This is because the potential of land and building tax is quite high along with regional decentralization performed. In this research, the observation data was done in 2005-2012 in the city of Pontianak. From this research, we expected can provide information for the public and for the evaluation of local government. Based on information and data, showing that the realization and growth of Land and Building Tax in Pontianak fluctuated even negative, and dont reach the target almost every year. Besides the viewed of the indicator, the first and second indicator is land and building tax was not optimal, only three indicators that were optimal. It can be concluded that the Land and Building tax income in the city of Pontianak has not reached its optimal value, because the indicators established by the local government has not fulfilled well or not yet achieved in accordance with the desired. Keywords : Optimalization, Land and Building Tax (PBB)